Tuning the surface structure and phase structure of PtCu3 nanoparticle for highly efficient electrocatalysts. (5th June 2022) - Liu, Feng; Gao, Yong; Ouyang, Xuan; Wang, Xinzhong; Li, Xuejiao; Han, Fuxie; Li, Wei; Tan, Feng; Zhou, Liexing; Yang, Xikun
Abstract: Significantly improving the catalytic activity and durability of platinum (Pt) based electrocatalysts is crucial for commercial application of fuel cells by tuning structure of Pt alloy nanoparticles. Here, we report a method of tuning structure of PtCu3 alloy nanoparticle by annealing in different atmospheres. The detailed analyses showed that evolution of surface structure and phase structure of PtCu3 alloy nanoparticles heat-treated in N2 atmosphere and N2 /H2 mixed atmosphere are mainly as follows: (1) when heat-treated in N2, the crystal phase of PtCu3 has undergone a transformation from disordered PtCu3 alloy to ordered PtCu3 alloy and then to disordered PtCu3 alloy with the increase of holding time from 30 min to 90 min; (2) when heat-treated in H2 /N2, a Pt-rich surface is formed on the Pt–Cu nanoparticles due to Pt segregation induced by H2 adsorption. Electrochemical measurements demonstrated that both PtCu3 /C-N2 electrocatalysts prepared in N2 and PtCu3 /C-N2/H2 electrocatalysts prepared in H2 /N2 exhibit enhanced mass activities toward the oxygen reduction reaction (ORR) relative to Pt/C electrocatalyst in acidic media. In particular, when the holding time is 90 min, the obtained PtCu3 /C-N2/H2 electrocatalysts with Pt-rich surface showed highest mass activity of 435 mA/mgPt (at 0.9 V vs. RHE), which is four times greater than that of Pt/C catalyst (20 wt.% Pt, 115 mA/mgPt ). This study provides a promising method for the reasonable design and preparation of low cost and high performance Pt-based electrocatalysts. Highlights: Surface and phase structure of PtCu3 nanoparticle are tuned by annealing in different atmospheres. Crystal phase of PtCu3 heat-treated in N2 gas has undergone a transformation from disorder to order. Formation of Pt-rich surface on Pt–Cu nanoparticles due to Pt segregation induced by H2 adsorption. The PtCu3 /C catalyst with Pt-rich surface exhibits a higher ORR activity compared to Pt/C catalyst.